Evaluation of the Physical and Mechanical Characteristics of Box Leather for Footwear Upper Applications Based on SNI 0234:2009: Implications for Industrial Ergonomics - Himawan Santoso; Wahyu Fajar Winata; Fauzi Ashari (Industrial Innovation, 2026)
Box leather is one of the most widely used chrome-tanned leathers for footwear upper applications due to its excellent combination of mechanical strength, flexibility, and surface quality. This study aimed to evaluate the physical and mechanical characteristics of box leather for footwear upper applications based on the requirements of SNI 0234:2009 and to discuss their implications from the perspective of industrial ergonomics. A descriptive research approach was employed through laboratory testing, including organoleptic assessment, thickness, tear strength, tanning maturity, finish rub fastness, water absorption, tensile strength, elongation at break, softness, crack resistance, burst resistance, and flex resistance, following the procedures specified in SNI 0234:2009. The results showed that most of the evaluated parameters complied with the standard requirements. The leather exhibited a thickness of 1.30 mm, tear strength of 52.38 kg/cm, tensile strength of 1653.26 kg/cm², elongation at break of 60.49%, and satisfactory crack resistance, burst resistance, and flex resistance, all of which fulfilled the requirements of SNI 0234:2009. However, water absorption after 2 h (89.69%) and 24 h (100.35%), grain adhesion (nerf), and wet finish rub fastness did not fully satisfy the standard and therefore require further improvement. From an industrial ergonomics perspective, the excellent mechanical performance indicates that the evaluated box leather possesses sufficient flexibility, structural stability, and resistance to repetitive loading, making it suitable for footwear upper applications that demand long-term comfort and durability. Conversely, the relatively high water absorption may reduce user comfort by increasing moisture retention and footwear weight during prolonged use. Overall, the evaluated box leather demonstrated good conformity with SNI 0234:2009, with future improvements recommended for moisture resistance, grain adhesion, and finishing performance through optimization of the retanning and finishing processes